Robert v. Gustin, The Revised Municipal Code of East St. Louis of 1908, at 361, § 885 (1909) - (:unkn) unknown (My University, 1908)
Chapter 39-Misdemeanors, Article 1-Offenses Affecting the Public Peace and Quiet, § 885: Prohibited concealed carry of any pistol, revolver, slungshot, metallic knuckles, Bowie-knife, dirk, razor, or other dangerous or deadly weapon. Also prohibited brandishing such weapons. Violators fined not less than twenty-five nor more than two hundred dollars.
Keywords: BRANDISHING; CARRY - CONCEALED